Integration of points cloud data from airborne and terrestrial laser scanner - Baharuddin, Nurul Zaitul Syeema (2016)
The purpose of this study is trying to solve the shortage of the data due to the limitations of the laser scanner instrument in data collection. The data integration between ALS with TLS are able to provide complete data for used by other applications such as 3D model of building, 3D model of forestry mapping, documentation of historical building, forensic and many more. The scope of this study focusing on the scanning the UTM Eco-Home building using ALS and TLS. The UTM Eco-Home building was chosen because it has a unique design and structure that can be test the capabilities of the laser scanner instruments. The ALS used to scan the roof top of the building and the TLS used to scan the façade of the building. The laser scanner instruments are used in data collection are to ensure that is no part of the building are missed to scan. After completing scanning the UTM Eco-Home building process, the dataset used for integration through registration method using man-made. The man-made is chosen because the characteristic of man-made can be seen in both dataset. The level of accuracy is assessed by comparison method with the conventional measurement using total station. The result from the integration is using for many purposes for example 3D city modelling, 3D forestry mapping, 3D topographic mapping, historical documentation and others.